Sosialisasi Tips dan Trik Membuat Pembelajaran Matematika yang Dianggap Membosankan Menjadi Lebih Inovatif di MIS Darul Mustofa, Jember - Muhlisatul Mahmudah; Tri Novita Irawati; Mely Agustin Reni Pitasari; Dwi Septy Arifannah; Linda Sri Wahyuni; Najhan Khoirunnisa (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Mathematics is often considered a difficult subject, full of formulas, and boring. This stigma affects students' motivation and engagement in the learning process. This community service activity aims to educate teachers and students about various innovative strategies that can be used to make mathematics learning more enjoyable through the use of interactive digital media. The implementation methods include interactive lectures, hands-on practice with applications (Kahoot, Quizizz, Mentimeter, Spin Wheel, and Gimkit), and reflection sessions. The results of the activities show positive changes: teachers gain new perspectives for creative teaching, while students show enthusiasm, courage to participate, and a reduced fear of mathematics. Thus, it can be concluded that the application of digital innovations in mathematics learning not only enhances learning motivation but also creates a more vibrant classroom atmosphere, interactive and meaningful.